Topiramate in Lennox-Gastaut Syndrome - J Gordon Millichap (Pediatric Neurology Briefs, 1999)
The efficacy and safety of topiramate as adjunctive therapy for Lennox-Gastaut syndrome were studied in an 11-week multicenter, double-blind, placebo-controlled trial involving 98 patients, 1-30 years of age, and reported from the New Jersey-Robert Wood Johnson Medical School, New Brunswick, NJ.